Rigid Polyurethane Foam Reinforced Coconut Coir Fiber Properties - Azmi, Mohd Azham (International Journal of Integrated Engineering, 2012)
This research work studied the properties of composite foam panels. Coconut coir fibers were used as reinforcement in polyurethane (PU) foam in order to increase the properties of foam. This composite foam panels were fabricated by using polyurethane molded method. The polyurethane foam panels reinforced from 5 to 20wt% coconut coir were produced to investigate the physical and mechanical test via density test and three point bending test respectively. It was found that the density test results show the composite foam panel density decreases as fiber content increased. The composite foam panels with 15 wt% coconut coir fibers offered less density with average value of 76.78 kg/m3. Result from mechanical test shows that the flexural properties were increased at 5wt % of coconut coir fiber with average value of maximum force and shear stress at 88N and 60 KPa. It was revealed that the coconut coir fibers at 5wt% significantly increased the physical and mechanical properties of composites foam panel.